Use of virtual reality in port implantation to reduce perioperative anxiety and pain: protocol for a randomised controlled pilot trial at a single German university hospital (VIP-trial; DRKS00028508) - Christoph W Michalski; Felix J Hüttner; Colette Dörr-Harim; Sandra Graf; Hannah Feldmann; Lisa S Hunold; Kira C Steinkraus; Nadir Nasir (BMJ Open)
Introduction Intravenous access port implantation is commonly performed under local anaesthesia, which offers advantages such as increased patient satisfaction and resource savings compared with general anaesthesia. However, patients may experience increased perioperative stress and anxiety in the operating room setting without general anaesthesia. Virtual reality (VR) distraction or hypnosis during surgery under local anaesthesia may help patients to auditorily and visually separate from their real environment and engage with a virtual environment through hypnorelaxing guidance. Previous studies suggested that VR hypnosedation may reduce the use of sedatives or general anaesthesia, and may offer additional benefits such as reducing postoperative pain and nausea, and promoting faster patient discharge.Methods and analysis The VIP trial is a randomised controlled pilot trial comparing the usage of VR during port implantation with the current standard of care (local anaesthesia and analgosedation if needed). A total of 120 adult patients are included after screening for eligibility and obtaining informed consent. Patients are randomised preoperatively in a 1:1 ratio to the trial groups. The main outcomes are change of perioperative anxiety and pain. Further outcomes include patient satisfaction and tolerability, perioperative analgesia and sedation, occurrence of postoperative nausea, vomiting and VR sickness symptoms, surgeon’s satisfaction, procedure duration, postoperative complications until postoperative day 30 and patient willingness to hypothetically undergo port implantation again under the same conditions.Ethics and dissemination The VIP trial has been approved by the Ethics Committee of the Medical Faculty of Ulm University (reference number 03/22). If the intervention demonstrates that VR can effectively reduce perioperative anxiety and pain, it may become a novel standard of care to minimise the need for analgosedation or general anaesthesia in port implantation procedures and improve patient outcomes. The results will be submitted to a peer-reviewed journal in the field and will be presented at applicable conferences to ensure rigorous evaluation and access for the academic community.Trial registration number German Clinical Trials Register: DRKS00028508; registration date 15 March 2022; Universal Trial Number: U1111-1275-4995.